Collaborative study to evaluate the indigestible neutral detergent fiber and indigestible acid detergent fiber contents in feeds by in situ procedure - De Souza, Marjorrie Augusto; Detmann, Edenio; Rocha, Gabriel Cipriano; De Oliveira Franco, Marcia; Batista, Erick Darlisson; De Campos Valadares Filho, Sebastião; Berchielli, Telma Teresinha [UNESP] (Universidade Estadual de Londrina, 2016)
The objective of this collaborative study was to evaluate the indigestible neutral detergent fiber (iNDF) and indigestible acid detergent fiber (iADF) content in feeds in six laboratories from institutions linked to the National Institute of Science and Technology in Animal Science (INCT-CA). Six feeds were evaluated: signal grass hay, sugarcane, corn silage, soybean meal, corn and citrus pulp. Estimated levels of iNDF and iADF proved to be dependent on the laboratory in which the analysis was performed. It was found that differences between laboratories ranged from 2.40 percentage points for soybean meal to 8.05 percentage points for sugarcane for iNDF analysis and from 1.79 percentage points for corn to 10.06 percentage points for hay for iADF analysis. It was observed in the individual evaluation of each material that total random variation of the results between laboratories ranged from 88.75 to 96.77% and 88.75 to 98.40% for iNDF and iADF analysis, respectively. The iNDF and iADF levels are dependent on the interaction effect between the evaluated material and laboratory and have low reproducibility; this may be a consequence of the differences between the methods practiced by each laboratory, demonstrating lack of standardization of procedures used by the laboratories.
Keywords: Analytical methods; Feed analysis; Indigestible fiber; Repeatability; Reproducibility